Association between the serum glucose-to-potassium ratio and clinical outcomes in ischemic stroke patients after endovascular thrombectomy - Zhang, Qianqian; Huang, Zhihang; Chen, Shuaiyu; Yan, E.; Zhang, Xiaohao; Su, Mouxiao; Zhou, Junshan; Wang, Wei (Frontiers in Neurology, 2024)
The baseline glucose to potassium ratio (GPR) is implicated for a poor outcome in patients with acute brain injury and intracranial hemorrhage. However, the impact of serum GPR on clinical outcomes after endovascular thrombectomy (EVT) treatment is unclear. This study aimed to evaluate the association between GPR at admission and functional outcome at 90 days after EVT. Methods: We retrospectively reviewed our database for patients with acute ischemic stroke with an anterior circulation large vessel occlusion who received EVT between October 2019 and December 2021. The baseline serum GPR was measured after admission. The primary outcome was 90-day poor outcome, which was defined as a modified Rankin Scale score of 3-6. Results: A total of 273 patients (mean age, 70.9 ± 11.9 years; 161 male) were finally included for analyses. During the 90-day follow-up, 151 (55.3%) experienced an unfavorable outcome. After adjusting for demographic characteristics and other potential confounders, increased GPR was significantly associated with a higher risk of 90-day poor outcome (odd ratios, 1.852; 95% confidence interval, 1.276-2.688, P=0.001). Similar results were observed when the GPR was analyzed as a categorical variable. In addition, the restricted cubic spline observed a positive and linear association of GPR with poor outcome at 90 days (P=0.329 for linearity; P=0.001 for linearity). Conclusions: Our study found that ischemic stroke patients with higher GPR at admission were more likely to have an unfavorable prognosis at 3 months, suggesting that GPR may be a potential prognostic biomarker for ischemic stroke after EVT.